Evaluation of the Use of Gamification in Language Learning for Students in Indonesia - Mohzana Mohzana (Yayasan Adra Karima Hubbi, 2023)
Background. With the development of technology and students' preferences for digital interactions, gamification offers an attractive alternative in increasing the effectiveness of language learning. However, understanding the influence of gamification, especially on students in Indonesia, is something that has not been fully explored. Purpose. This research aims to evaluate the use of gamification in language learning for students in Indonesia. Research focus includes increasing motivation, engagement levels, and language learning outcomes. In addition, this research is intended to provide a solid foundation for the development of more innovative and effective learning strategies at the tertiary level in Indonesia. Method. This research adopts a quantitative approach with survey methods. A total of 40 Arabic student respondents from various universities in Indonesia were selected purposively. The sampling method involved distributing questionnaires via Arabic student WhatsApp groups. Data collection was carried out through a special questionnaire designed with Google Form. Data analysis refers to the Miles Huberman approach, including descriptive and inferential data processing. Results. The research results show variations in the level of student knowledge about gamification, with the majority giving positive responses. Although most students experience additional motivation, there are concerns regarding an overemphasis on the end result rather than the learning process. Conclusion. Gamification in language learning makes a positive contribution to student motivation, engagement, and enjoyment. However, the main challenge is the risk of overemphasis on the bottom line. The implementation of gamification needs to be adapted to the characteristics and needs of students, maintaining a balance between the game aspect and the essence of language learning. In conclusion, this research provides an in-depth understanding of the impact of gamification on Arabic language students in Indonesia, with the potential to provide guidance for the development of more effective language learning practices in higher education